ARTIFICIAL INTELLIGENCE APPLICATION IN ENGLISH SPEAKING CLASS: STUDENTS’ VIEW AND OBSTACLES - Syafryadin Syafryadin (Scopus ID 57212212579, WoS ID: ABI-8120-2020) (IKIP Siliwangi, 2024)
This study aims to find students’ view towards the implementation of Artificial intelligence (AI) in learning speaking and its obstacles. Mixed method was used to conduct this research. the total population is 105 students. While, the sample of this study was thirty five students of English Education Department, Bengkulu University, Indonesia. It was just because only class C that the lecturer implemented Artificial intelligence application in public speaking class. Thus, the sampling technique was purposive sampling. Questionnaire and interview were addressed as instruments to answer the research questions. The questionnaire was addressed to thirty five students, while only fifteen students were interviewed. The data were analyzed quantitavely and qualitatively. For quantitative analysis, the data were analyzed by using simple calculation to know the percentage and mean score. For qualitative data analysis, coding was used for it. The result showed that students had positive responses towards the implementation of Artificial Intelligence in English speaking calss. However, few students faced several obstacles in applying in it when they spoke English. Those obstacles were poor internet connection, incomplete feature of the AI application, language skill and psychological problem. In short, AI applications can be as one of media for students in learning speaking because it helps them for speaking, even though, those still have limitation.